Exploring women's experiences of abuse and communication within intimate heterosexual relationships in a low-income semi-rural community - Gardiner, Desiree (Department of Psychology, 2023)
This study is a qualitative exploration of women's experiences of abuse and communication within intimate relationships. How women remain in abusive relationship is explained by how they construct and give meaning to the relationship. Strategies for surviving and resisting the abuse, women's perceptions of the abuse; as well as how they construct communication in the relationship, are discussed. Interviews were conducted with 15 women, who volunteered to participate in this study and self-identified as being involved with a physically abusive partner. All the participants were from a particular low-income, semi-rural community in South Africa. Narrative analysis, with particular emphasis on language and discourse, was conducted on unstructured interviews regarding women's relationships with their partners. Interview topics included daily problems, the presence of drugs or alcohol, communication between partners, and their experiences and responses to violence. Women described the different types of abuse they experienced; how they made sense of it; and their attempts to prevent the abuse from occurring. Women also constructed themselves and their partners within particular gender identities and cultural frameworks. The socio-cultural context provided a filter through which women understood their experiences of abuse. Dominant male and female norms were both adopted and resisted by participants, and expressed when women spoke of their interaction and communication with their partners.